The Influence of Principalsâ Leadership Styles on School Innovation in Jambi (Case Study in Several Senior High Schools in Jambi) - Samsu, Samsu; Rusmini, Rusmini (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
School leadership styles that affect school innovation is essential to bring schoolsâ changes. This study aimed to determine school leadership styles and its effect on school innovation at the senior high school level in Jambi city. This study uses ten leadership styles, they are participative, laissez faire, authoritarian, democratic, charismatic, transformational, situational, trust, grid, and three-dimensional leaderships. The framework of the research are developed by associating ten leadership styles with school innovations including (1) the principals role in doing innovation in the schools, (2) the forms of innovation implemented in the areas of academic achievement, (3) the form of innovations carried out in the field sports and (4) the form of innovations implemented in the institutional field, and (5) the forms of innovation undertaken in the field of schoolâ culture. There are 32 teachers and 32 principals were taken as samples. This study used mixed methods research. Data were analyzed using mean, standard deviation, and correlation. The results showed that the overall principals leadership style is not sufficient to affect senior high school innovation in Jambi city, this is evidenced by there are only three of those ten leadership styles have positive relationship when they are doing schoolâs innovations in Jambi city. Thus, the principals should give attention to all the leadership styles to do innovation at senior high school in Jambi city to improve the quality of schools.